Phenomenological Revision of Social Creativity in Educational Institutions during the War in Ukraine after February 24, 2022 - Terepyshchyi, Serhii (Studia Warmińskie, 2024)
This article presents a phenomenological study of social creativity within Ukrainian educational institutions during the war that began on February 24, 2022. Involving 153 participants across ten regions, the research explores how educators and students adapted to the challenges of conflict through innovative teaching methods and student-led initiatives. Grounded in the philosophies of Husserl, Heidegger, and Merleau-Ponty, the study identifies key themes of resilience, community solidarity, and innovation born out of necessity. The findings reveal that social creativity served as a means of transcendence, enabling individuals to assert agency and find meaning despite adversity. Educators embraced hybrid learning models and community-based teaching, while students engaged in peer teaching and digital resource creation. These efforts not only maintained educational continuity but also strengthened communal bonds. Aligning with prior research on displaced scholars and adaptive education in conflict zones, the study underscores the critical role of creativity in fostering resilience and sustaining education during crises. It highlights the importance of nurturing creativity within curricula to prepare individuals for complex and unpredictable realities. The insights offer a hopeful outlook for the future of Ukrainian education and provide valuable lessons for other societies facing similar challenges.